Corn straw-saccharification fiber improved the reproductive performance of sows in the late gestation and lactation via lipid metabolism - Liu, Mengjie; Liu, Chaoqi; Shi, Jiajia; Wang, Ping; Chang, Juan; Xu, Xiaoxiang; Wang, Lijun; Jin, Sanjun; Li, Xinxin; Yin, Qingqiang; Zhu, Qun; Dang, Xiaowei; et al. (Frontiers in Nutrition, 2024)
With the development of animal husbandry, the shortage of animal feedstuffs has become serious. Dietary fiber plays a crucial role in regulating animal health and production performance. The aim of this study was to investigate the effects of three kinds of corn straw-saccharification fibers (CSSF) such as high-fiber and low-saccharification (HFLS), medium-fiber and medium-saccharification (MFMS), low-fiber and high-saccharification (LFHS) CSSF on the reproductive performance of sows. Thirty-two primiparous Yorkshire sows were randomly assigned to 4 groups, 8 sows for each group. Group A was the basal diet as the control group; groups B -D were added with 6% HFLSCSSF, 6% MFMSCSSF and 6% LFHSCSSF to replace some parts of corn meal and wheat bran in the basal diet, respectively. The experimental period was from day 85 of gestation to the end of lactation (day 25 post-farrowing). The results showed that 6% LFHSCSSF addition could significantly increased number of total born (alive) piglets, litter weight at birth (P < 0.05), whereas three kinds of CSSF could significantly decreased backfat thickness of sows during gestation (P < 0.001), compared with the control group. Furthermore, CSSF improved the digestibility of crude protein, ether extract and fiber for sows. In addition, the levels of total cholesterol, total triglycerides,